Importance and added value of functional impairment to predict mortality: a cohort study in Swedish medical inpatients - Gustav Torisson; Elisabet Londos; Lars Stavenow; Lennart Minthon (BMJ Open)
Background Accurate estimation of prognosis in multimorbid hospital patients could improve quality of care. This study aims to determine the relative importance and added value of a performance-based activities of daily living (ADL) measure with regard to mortality prediction.Methods 200 inpatients, aged over 60 years, were recruited at the Department of General Internal Medicine at a tertiary university hospital. Two nested survival models were built, one with established risk factors (age, sex, Charlson comorbidity index, haemoglobin, albumin, body mass index and glomerular filtration rate), and one using the same covariates with the Gottfries-Bråne-Steen (GBS)-ADL measure added. The relative importance of GBS-ADL was evaluated in the full model. The added value of GBS-ADL was determined by comparing the nested models using four approaches: difference in overall χ2, discrimination, continuous net reclassification index (NRI >0) and integrated discrimination improvement (IDI).Results In the full model, GBS-ADL was the single most important predictor of mortality (χ2-df=30, p<0.001). The likelihood ratio χ2 test showed significant added value of ADL (p<0.001). The C-statistic was 0.78 with ADL and 0.72 without (difference 0.058, 95% CI 0.022 to 0.094). The NRI >0 was 0.42 (95% CI 0.20 to 0.58) and IDI 0.15 (95% CI 0.07 to 0.22).Conclusions Compared with a set of available clinical risk factors, impairment in ADL was a stronger predictor of all-cause mortality, showing substantial added value. Implementing quantitative ADL measurements could enable more appropriate and individual care for the elderly.